Hubungan BBLR dengan Kekurangan Gizi (Wasting) Pada Anak Usia 6-23 Bulan - Aprilya Roza Werdani (Pusat Riset dan Inovasi Nasional, 2021)
Malnutrition is a form of malnutrition caused by inadequate food intake and recurrent infectious diseases. This study aims to determine the relationship between LBW and the incidence of wasting in children aged 6-23 months in Pagedangan District, Tangerang Regency in 2020. The research design used was cross-sectional. Malnutrition (wasting) is measured using the indicator body weight according to body length (BB/PB). Data collection was carried out by anthropometric measurements (body weight and length) and questionnaire interviews with respondents (mothers of research subjects). The results of the study showed that 17.0% of children aged 6-23 months in Pagedangan District, Tangerang Regency experienced wasting. Out of 153 children aged 6-23 months, 52.9% did not reach the minimum acceptable diet, 32.0% had a deficit in energy intake, and 52.9% had a deficit in protein intake. The results of the chi-square analysis showed that the incidence of LBW had a significant relationship with malnutrition (wasting). Multiple logistic regression tests show that energy intake is the dominant factor for wasting in children aged 6-23 months in Pagedangan District, Tangerang Regency in 2020 (OR=5.616; 95% CI: 1.193-26.438).